The Coda Voicing Contrast in Lithuanian Learners’ English - Bikelienė, Lina; Vaitkevičiūtė, Milda (Verbum, 2018)
[full article and abstract in English]Vowel duration, though not belonging to the three main factors in the decription of vowels, plays an important role in the English language. Alongside qualitative differences, it helps to distinguish between the meaning of such words as ‘ship’ and ‘sheep’. Vowel duration has been recognised to be a complex phenomenon, which depends on a combination of factors: internal and external (Delattre 1962). The present pilot study focuses on one of the factors belonging to the latter group, i.e. the influence of the postvocalic voicing on vowel duration in minimal pairs of one sylable CVC (consonant-vowel-consonant) words, a phenomenon reffered to as ‘pre-fortis clipping’ (Wells 1990), ‘voicing effect’ (Yoneyama and Kitahara 2014), ‘consonantal voicing effect’ (Beller-Marino 2014), ‘vowel-length effect’ (Ko 2007), ‘shortening’ (Cruttenden 2014), ‘post-vocalic consonant voicing effect’ (Taubeber and Evanini 2009), etc. The scope of this research was limited to four checked unrounded English monophthongs: the front-central, close-mid /ɪ/, the front, mid /e/, the front, open /æ/, and the central, open-mid /ʌ/. The durational differences were analysed from a perceptive and productive perspectives. The obtained results indicated that the Lithuanian learners showed an effect of voicing on vowel-duration, manifested in a number of languages: the mean duration of the examined vowels was shorter before a fortis than before a lenis coda. The analysis of individual students’ production data proved the importance of the individual variable.
Keywords: vowel duration; coda voicing; Lithuanian learners’ English